The DNA methylation landscape of giant viruses - Sandra Jeudy (Nature Communications, 2020)
DNA methylation is an epigenetic marker in all domains of life. Here, Jeudy et al., using single-molecule realtime sequencing, determine DNA methylation patterns in giant viruses and evolutionary analysis of virus encoded DNA methyltransferases suggests that they affect viral fitness.